2014
DOI: 10.1002/adsc.201301157
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐Catalyzed and Promoted Reactions of H‐Phosphinate Esters

Abstract: H-Phosphinates react with alkenes and alkynes using catalytic manganese(II) acetate. Under stoichiometric conditions with manganeseA C H T U N G T R E N N U N G (III) acetate or with catalytic manganese(II) acetate + excess manganese(II) oxide various reactions like arylation or cyclization through radical oxidative arylation can take place. Whereas the chemistry of manganese is already well developed for the functionalization of H-phosphonates, the present methodology provides an unprecedented access to funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Han and Zhao reported that radical reactions of optically pure (R P )-alkylphenylphosphinates 385 in a stereospecific fashion (Scheme 163) 265. The Montchamp group employed alkyl phosphonyl radicals for hydroalkylsphonylation of alkenes.The radicals generated form the treatment of ethyl alkylphosphinates with Mn(OAc) 3 were reacted with the alkenes without solvent to form products 386 (Scheme 164) 266. …”
mentioning
confidence: 99%
“…Han and Zhao reported that radical reactions of optically pure (R P )-alkylphenylphosphinates 385 in a stereospecific fashion (Scheme 163) 265. The Montchamp group employed alkyl phosphonyl radicals for hydroalkylsphonylation of alkenes.The radicals generated form the treatment of ethyl alkylphosphinates with Mn(OAc) 3 were reacted with the alkenes without solvent to form products 386 (Scheme 164) 266. …”
mentioning
confidence: 99%
“…Our initial reaction (Scheme , Intermolecular) employed OctP(O)(OCy)H as a standard model H ‐phosphinate ester, Mn(OAc) 3 (2 equiv), and benzene in large excess. The phosphinate product was obtained in 37% yield . While mediocre, this yield is not very different from Effenberger's 48% with (EtO) 2 P(O)H (2 equiv), AgNO 3 (20 mol %), Na 2 S 2 O 8 (5 equiv) and benzene (1 equiv) …”
Section: Mn(oac)3‐promoted Reactionsmentioning
confidence: 68%
“…The intramolecular version was examined for the synthesis of P ‐heterocycles (Scheme , Intramolecular) . As expected for a cyclization, the yields were moderate to good.…”
Section: Mn(oac)3‐promoted Reactionsmentioning
confidence: 99%
See 2 more Smart Citations